Magnesium‐Catalyzed Tandem Dehydrogenation‐Dehydrocoupling: An Atom Economical Access to Alkynylboranes. Issue 15 (5th March 2020) - Birepinte, Mélodie; Liautard, Virginie; Chabaud, Laurent; Pucheault, Mathieu
Abstract: Owing to the unusual reactivity of sterically hindered amine–borane complexes, a catalytic system based on magnesium salts was designed to perform a tandem dehydrogenation–dehydrocoupling between terminal alkynes and boranes. The reaction is providing pure alkynylboranes within few minutes at room temperature, with only two molecules of hydrogen as a byproduct. Abstract : A tandem made for two : An efficient synthesis of alkynylaminoborane was developed using a magnesium catalyst at room temperature. The reaction proceeds within few minutes in high yields releasing hydrogen through a tandem dehydrogenation/dehydrocoupling original mechanism between terminal alkynes and boranes.